Dehydrozingerone Exhibits Synergistic Antifungal Activities in Combination with Dodecanol against Budding Yeast via the Restriction of Multidrug Resistance - Yamawaki, Chika; Yamaguchi, Yoshihiro; Ogita, Akira; Tanaka, Toshio; Fujita, Ken-ichi (Planta Medica International Open, 2018)
Drug resistance in fungal infections has been a more frequent occurrence with the increasing number of immunocompromised patients. In efforts to overcome the problem of fungal drug resistance, we focused on the phenolic compound dehydrozingerone, which is isolated from Zingiber officinale. The effectiveness of this compound on the model yeast Saccharomyces cerevisiae has not been reported. In our study, dehydrozingerone showed a weak antifungal activity against the yeast, but demonstrated a synergistic effect in combination with dodecanol, which typically only restricts cell growth transiently. Efflux of rhodamine 6G through the multidrug efflux pumps was significantly restricted by dehydrozingerone. The transcription level of PDR5, encoding a primary multidrug efflux pump in S. cerevisiae, was enhanced with dodecanol treatment, whereas the level was reduced by dehydrozingerone. These results suggest that dehydrozingerone may be effective for potentiating antifungal activity of other drugs that are expelled from fungi by multidrug transporters like Pdr5p.
Keywords: ABC transporter; antifungal; dehydrozingerone; feruloylmethane; multidrug resistance; PDR5; Saccharomyces cerevisiae; vanillylidenacetone